Not so Smart: On Smart TV Apps - Niemietz, Marcus; Somorovsky, Juraj; Mainka, Christian; Schwenk, Jorg (International Workshop on Secure Internet of Things (SIoT))

How to Break XML Encryption -- Automatically - Kupser, Dennis; Mainka, Christian; Schwenk, Jö; Somorovsky, Juraj (9th USENIX Workshop on Offensive Technologies (WOOT 15))

Revisiting SSL/TLS Implementations: New Bleichenbacher Side Channels and Attacks - Meyer, Christopher; Somorovsky, Juraj; Weiss, Eugen; Schwenk, Jörg; Schinzel, Sebastian; Tews, Erik (23rd USENIX Security Symposium (USENIX Security 14))

On the insecurity of XML Security - Somorovsky, Juraj
XML Encryption and XML Signature describe how to apply encryption and signing algorithms to XML documents. These specifications are implemented in a wide range of systems and frameworks processing sensitive data, including banking, eGovernment, eCommerce, military, and eHealth infrastructures. The article presents practical and highly critical attacks which allow to forge signed XML documents or reveal contents of encrypted XML data.

A New Approach towards DoS Penetration Testing on Web Services - Falkenberg, Andreas; Mainka, Christian; Somorovsky, Juraj; Schwenk, Jörg (2013 IEEE 20th International Conference on Web Services)

Penetration test tool for XML-based web services - Mainka, Christian; Mladenov, Vladislav; Somorovsky, Juraj; Schwenk, Jörg (CEUR Workshop Proceedings)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

On Breaking SAML: Be Whoever You Want to Be - Somorovsky, Juraj; Mayer, Andreas; Schwenk, Jörg; Kampmann, Marco; Jensen, Meiko (Presented as part of the 21st USENIX Security Symposium (USENIX Security 12))

Technical Analysis of Countermeasures against Attack on XML Encryption -- or -- Just Another Motivation for Authenticated Encryption - Somorovsky, Juraj; Schwenk, Jörg (2012 IEEE Eighth World Congress on Services)

Bleichenbacher’s Attack Strikes again: Breaking PKCS#1 v1.5 in XML Encryption - Jager, Tibor; Schinzel, Sebastian; Somorovsky, Juraj (Computer Security – ESORICS 2012)